The Pedagogical Meaning of the Crusade for the Liberation of Man - Paweł Kaźmierczak (Nicolaus Copernicus University in Toruń, 2017)
Crusade for the Liberation of Man is one of the organizational forms of teetotalism, initiated by Father Franciszek Blachnicki. The article discusses the following issues: a) a theoretical basis for Fr. Blachnicki's idea of teetotalism, b) organizational forms of his teetotalist activities, c) practical conditions of membership in the Crusade for the Liberation of Man, and d) conclusions regarding the pedagogical impact of the Crusade.